Sensitizing Clostridium difficile Spores With Germinants on Skin and Environmental Surfaces Represents a New Strategy for Reducing Spores via Ambient Mechanisms - Michelle Marie Nerandzic; Curtis J. Donskey (Case Western Reserve University, 2017)
Background: Clostridium difficile is a leading cause of healthcare-associated infections worldwide. Prevention of C. difficile transmission is challenging because spores are not killed by alcohol-based hand sanitizers or many commonly used disinfectants. One strategy to control spores is to induce germination, thereby rendering the spores more susceptible to benign disinfection measures and ambient stressors. Methods/Results: C. difficile spores germinated on skin after a single application of cholic acid-class bile salts and co-germinants; for 4 C. difficile strains, recovery of viable spores from skin was reduced by ~0.3 log10CFU to 2 log10CFU after 2 hours and ~1 log10CFU to >2.5 log 10CFU after 24 hours. The addition of taurocholic acid to 70% and 30% ethanol significantly enhanced reduction of viable spores on skin and on surfaces. Desiccation, and to a lesser extent the presence of oxygen, were identified as the stressors responsible for reductions of germinated spores on skin and surfaces. Additionally, germinated spores became susceptible to killing by pH 1.5 hydrochloric acid, suggesting that germinated spores that remain viable on skin and surfaces might be killed by gastric acid after ingestion. Antibiotic-treated mice did not become colonized after exposure to germinated spores, whereas 100% of mice became colonized after exposure to the same quantity of dormant spores. Conclusions: Germination could provide a new approach to reduce C. difficile spores on skin and in the environment and to render surviving spores less capable of causing infection. Our findings suggest that it may be feasible to develop alcohol-based hand sanitizers containing germinants that reduce spores on hands.